Novel insights into the epigenetics of diffuse glioma - Carla Danussi; Jason T. Huse (Molecular & Cellular Oncology, 2018)
Loss-of-function mutations of the chromatin regulator ATRX (α-thalassemia mental retardation X-linked) occur frequently in diffuse gliomas, but the molecular mechanisms by which ATRX inactivation promotes oncogenesis remain unclear. We recently reported that Atrx deficiency drives glioma-relevant phenotypes, such as increased motility and astrocytic differentiation profiles, by directly modulating epigenomic lanscapes in glioma cells of origin. Our work has significant implications on the role of epigenetic regulator dysfunction in the oncogenic process.